PARAMETERIZATION OF THE GENERALIZED PROCA THEORY IN GRAVITATIONAL WAVE - Marliana
The LIGO detector's detection of gravitational waves in 2015 proved the truth of Einstein's predictions in 1915. According to Einstein, if two massive objects orbit each other at high speeds, the motion will produce ripples that travel in spacetime as gravitational waves. The first gravitational waves detected resulted from the merging of two black hole systems called GW150914. The result of merging these black holes forms a black hole with a mass that is smaller than the total mass of the two. The rest of the mass propagates in space and time into gravitational waves. Furthermore, in 2017, gravitational waves were detected again from the merger of two neutron stars named GW170817 and GW170817A. The data obtained from these observations can be used to test the theories of gravity developed so far. The theory of gravity developed at this time was a modification of Einstein's general theory of relativity. This modification was made to answer various problems related to the universe's development. Many theories have been proposed, including modifying the material and curvature terms of Einstein's theory of gravity. It started from adding a scalar field to the curvature term to adding a vector field. The generalized Proca theory is a generalization of the Proca theory developed in 2014, similar to Horndeski's theory. Proca's generalized theory is a theory of gravity with second-order equations of motion that add a massive vector to gravitons. The Lagrangian is described by five vector functions containing arbitrary functions G2, G3, G4, and G5, whose structure is similar to the Horndeski model. Horndeski's theory is the most common form of the Lorentz invariant, which is the development of general relativity in four dimensions, constructed using a single scalar field with the equations of motion up to secondorder derivatives. This research was conducted to parameterize Proca's theory which was generalized with linearized theory with a weak field approach in the form of the gravitational wave equation. The energy-momentum tensor is obtained from the action equations of the generalized Proca theories, which is then derived to obtain the gravitational wave equation from the generalized Proca theory. This equation is derived to get the gravitational wave speed equation. Parameterization is done by applying constraints to arbitrary functions in the generalized Proca theory. It was found that G4 and G5 influenced the deviation of the gravitational wave speed on the speed of light, the mass of the graviton, and the change in the speed of the Planck mass.